Efficient energy control strategies for a Standalone Renewable/Fuel Cell Hybrid Power Source. (15th January 2015) - Bizon, Nicu; Oproescu, Mihai; Raceanu, Mircea
Highlights: A load – following control that operates the battery in charge – sustained mode. A real-time Maximum Efficiency Point Tracking control that saves hydrogen fuel. A comparative study of four strategies to control the fueling rates of the fuel cell stack. Four control strategy for the HPS under unknown RES and load power profile are analyzed. An increase of 3–5% of fuel efficiency was observed for the best strategy proposed. Abstract: In this paper, four energy control strategies are proposed and analyzed for the standalone Renewable/Fuel Cell Hybrid Power Source (RES/FC HPS). The concept of the load following (LF) and Maximum Efficiency Point Tracking (MEPT) is used to control the fueling rates. A standalone RES/FC HPS uses at least one Renewable Energy Sources (RES) and a Polymer Electrolyte Membrane (PEM) Fuel Cell (FC) as backup source. Photovoltaic (PV) array and wind turbines (WT) farm are used as RES and the surplus of energy during light load stages is stored in hydrogen tank via water electrolysis to fuel the PEMFC. Small-scale RESs and commercially available PEMFCs are interfaced to the common DC bus via power converters and then to the single-phase distribution grid through a voltage source inverter. RES/FC HPS seem to be an efficient alternative for supplying smart houses and isolated sites. This paper proposes a new supervision strategy of the Energy Management Unit (EMU) based on the LF control approach that assures a charge-sustaining (CS) mode for the Energy Storage System (ESS). So, the capacity of the batteries stack can be reduced at minimum if it is directly connected to the DC bus. The ultracapacitors stack compensates dynamically the power flow balance on the DC bus, regulating the DC voltage via a bidirectional buck-boost power converter. Thus, a semi-active hybrid topology is adopted for the ESS having the batteries stack. The MEPT loops ensure an optimized energy management of the RES/FC HPS. The LF strategy designed based on the power flow balance guarantees the load demand through the efficient management of the power flow from RES, FC and ESS, adapting FC energy production to load profile. The FC energy production is controlled via the fueling rates (one is controlled in the LF loop and the other is controlled in the MEPT loop) to maximize the energy consumption indicator: the ratio of the produced energy and the fuel consumed by the FC system during a load cycle. Thus, this paper evaluates the control performances of the four control topologies to fuel the FC stack during an variable RES and load profile. The MATLAB-Simulink® software package is used to model the RES/FC HPS and develop the four EMU strategies. Simulation results shown comparatively the performance of the EMU strategies proposed under different scenarios of RES power generation and load demand.